De: Jean Fréville, la nuit finit à Tours; Paris, 1951. Cachin prononçant son discours au Congrès de Tours
De: Jean Fréville, la nuit finit à Tours; Paris, 1951. Cachin prononçant son discours au Congrès de Tours.